Miniature electrochemical sensor as well as preparation method and application thereof

By forming a specific imprint cavity on the micro electrochemical sensor, the problem of insufficient detection sensitivity and selectivity of VEGF in the prior art is solved, and the detection of VEGF with high sensitivity and high selectivity is achieved.

CN119827602APending Publication Date: 2025-04-15JIAXING UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510042508.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art has problems of poor sensitivity and poor selectivity when detecting vascular endothelial growth factor (VEGF).

Method used

A micro electrochemical sensor based on surface molecular imprinted polymers and acupuncture needles is used to form a specific imprinted cavity by electrodepositing gold nanoparticles, multi-walled carbon nanotubes, polyferulic acid and other materials, thereby achieving high selectivity and high sensitivity detection of VEGF.

Benefits of technology

It realizes high sensitivity and selective detection of VEGF, has good detection performance and stability, and is suitable for biomedical research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827602A_ABST
    Figure CN119827602A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical sensors, and particularly relates to a miniature electrochemical sensor and a preparation method and application thereof. The miniature electrochemical sensor is a sensor based on a surface molecularly imprinted polymer and an acupuncture needle; the preparation method comprises the following steps: sequentially electrodepositing gold nanoparticles, multi-walled carbon nanotubes, polyferulic acid and gold nanoparticles on an acupuncture needle, incubating in a 4-mercaptophenylboronic acid solution, incubating in a vascular endothelial growth factor protein solution, sequentially electrodepositing poly (3-aminophenylboronic acid) and polychrome black T, and finally eluting the vascular endothelial growth factor protein to obtain the vascular endothelial growth factor. A specific imprinting cavity which is complementarily matched with the molecular structure of the vascular endothelial growth factor protein is formed. According to the invention, polyferulic acid is taken as an electroactive signal source, 3-aminophenylboronic acid and chrome black T are taken as functional monomers, an acupuncture needle sensing platform of a molecularly imprinted polymer is prepared through electrodeposition polymerization, a recognition sensing interface is formed, and high selectivity and high sensitivity are shown on vascular endothelial growth factors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical sensors, and specifically relates to a micro electrochemical sensor and a preparation method and application thereof. The micro electrochemical sensor is a sensor based on surface molecular imprinting polymers and acupuncture needles, and is used to monitor endothelial growth factor, a specific biomarker of vascular health. Background Art

[0002] Early diagnosis of diseases is conducive to timely intervention and treatment, improving the quality of life of patients and increasing the cure rate. Biomarkers are biological molecules such as DNA, RNA or protein that exist in organisms and are indicators of disease states and development processes in physiology or pathology. Biomarker monitoring indicators are often used for early diagnosis of diseases, early warning tracking, and reflection of treatment effects. Among the detection methods that have developed rapidly in recent years, biosensors have become important devices for indicating biomarkers, which have far-reaching scientific significance and broad development prospects.

[0003] The key sensing elements of sensors are often limited by the complex preparation process and extremely sensitive environmental conditions. Therefore, in recent years, artificial receptors have received more and more attention. Artificial receptors simulate biomimetic structures and imitate the recognition, binding and sensing properties of biological materials.

[0004] Vascular endothelial growth factor (VEGF) is characterized as a heparin-binding angiogenic growth factor that is specific to endothelial cells; VEGF is associated with angiogenesis in wound healing, diabetes, retinopathy, and rheumatoid arthritis. Abnormal VEGF concentrations in the blood (over 1 ng / mL) can be used as a diagnostic and prognostic marker for different types of tumors. Currently, antibody-based assays include ELISA, Luminex, and commercial VEGF detection kits. However, these assays all have technical defects such as poor sensitivity and selectivity for VEGF detection. Summary of the invention

[0005] Based on the above-mentioned deficiencies in the prior art, the present invention provides a micro-electrochemical sensor and its preparation method and application. The micro-electrochemical sensor of the present invention is a sensor based on surface molecular imprinting polymers and acupuncture needles. After gold nanoparticles, multi-walled carbon nanotubes, polyferulic acid, and gold nanoparticles are sequentially electrodeposited on the acupuncture needles, they are first incubated in a 4-mercaptophenylboric acid solution, then incubated in a vascular endothelial growth factor protein solution, and then poly-3-aminophenylboric acid and polychrome black T are sequentially electrodeposited, and finally the vascular endothelial growth factor protein is eluted to form a specific imprinted cavity that complements the molecular structure of the vascular endothelial growth factor protein. The present invention uses polyferulic acid as an electroactive signal source, uses 3-aminophenylboric acid and chrome black T as functional monomers, and prepares an acupuncture needle sensing platform of molecular imprinting polymers by electrodeposition polymerization to form a recognition sensing interface, which shows high selectivity and high sensitivity to the target analyte vascular endothelial growth factor.

[0006] The present invention is achieved by utilizing the following technical solutions:

[0007] The present invention provides a method for preparing a micro electrochemical sensor, comprising the following steps:

[0008] S1. In a typical processing process, the stainless steel acupuncture needle (AN) was polished in the same direction with fine sandpaper for 3 minutes to facilitate the subsequent modification steps. Next, the polished acupuncture needle was immersed in anhydrous ethanol and ultrasonically cleaned for 10 minutes. The treated acupuncture needle was immersed in ultrapure water for ultrasonic cleaning for 10 minutes and dried naturally in the air to obtain a bare needle electrode (ANE).

[0009] S2. Modify gold nanoparticles on the ANE tip using cyclic voltammetry: immerse the tip of the bare needle electrode in 2.5 mmol / L chloroauric acid solution for electrodeposition, use a saturated calomel electrode as the reference electrode, and a platinum wire as the counter electrode. Use cyclic voltammetry (CV) to cycle 3 to 5 times in the potential range of -1.5 to 0.5 V with a scan rate of 25 mV / s. After the deposition is completed, rinse the tip surface with ultrapure water to obtain ANE / AuNPs. The deposition of AuNPs provides a large specific surface area and high conductivity for subsequent modification.

[0010] S3, using constant current method to deposit carbon tubes: place the tip of ANE / AuNPs into a mixed solution of 2mg / L multi-walled carbon nanotubes (multi-walled carbon nanotubes are selected from c-MWNTs or MWNTs) and 0.02mol / L 3,4-ethylenedioxythiophene (EDOT) for deposition, using a saturated calomel electrode as a reference electrode and a platinum wire as a counter electrode, and deposit for 80-120s at a potential of 1.1-1.3V to obtain ANE / AuNPs / pEDOT-MWNTs. ANE / AuNPs modified with MWNTs have a large specific surface area and conductivity, and can be used as a good carrier for fixing SMIP; EDOT increases stability, and MWNTs alone are not very uniform and stable, and they form a film together after adding EDOT.

[0011] S4. FA was electropolymerized by the CV method. The needle tip of ANE / AuNPs / pEDOT-MWNTs was placed in a PBS solution (pH = 4.5) containing 0.4 mmol / L ferulic acid. A saturated calomel electrode was used as the reference electrode and a platinum wire was used as the counter electrode. The voltage was cycled in the range of -0.25 to 0.75 V for ≥10 cycles with a scanning rate of 20 mV / s (before starting the polymerization, the PBS solution of ferulic acid was bubbled with nitrogen and completely deoxygenated). ANE / AuNPs / pEDOT-MWNTs / pFA, abbreviated as ANE / / pFA, was obtained. pFA was the electroactive signal source. The pFA was built into the lower layer of the molecular imprint. The electrical signal was transmitted from the imprinting cavity. After the specific imprinting cavity was occupied by VEGF, the electrical signal of pFA would decrease, and there was a corresponding relationship with the concentration, thereby realizing the direct detection of vascular endothelial growth factor (VEGF).

[0012] S5. In order to better fix the modified protein later, it is necessary to deposit another layer of gold nanoparticles. The method is the same as step S2. The tip of ANE / / pFA is immersed in 2.5mmol / L chloroauric acid solution for electrodeposition. A saturated calomel electrode is used as the reference electrode and a platinum wire is used as the counter electrode. Cyclic voltammetry is used to cycle 3 to 5 times in the potential range of -1.5 to 0.5V with a scanning rate of 25mV / s. After the deposition is completed, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs are obtained.

[0013] S6. Place the needle tip of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs into 0.1mmol / L 4-mercaptophenylboric acid solution and incubate at 4℃ for 90~120min to obtain

[0014] ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA, 4-mercaptophenylboronic acid solution can form a weak bond force with VEGF and bind and anchor VEGF.

[0015] S7. Place the needle tip of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA in a VEGF protein solution (concentration of 10 μg / mL), incubate at 4°C for 7~9 hours to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF, and fix vascular endothelial growth factor on ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA.

[0016] S8, 3-aminophenylboronic acid (3-APBA) and chrome black T (EBT) are used as functional monomers, VEGF is a three-dimensional structure, 4-MPBA can only bind to one site of VEGF, 3-APBA contains a functional group that binds to VEGF, and can bind to other sites of VEGF; the outer layer of EBT has no binding force with VEGF, which reduces the specific adsorption of 3-APBA on VEGF, so that the specific imprinted cavity can selectively bind to VEGF. Molecular imprinting polymer SMIP is formed on the surface of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF by electropolymerization, and the sensing interface is successfully prepared. The formed detection platform shows high selectivity and high sensitivity to VEGF, specifically:

[0017] The needle tip of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF was immersed in 0.1 mol / L PBS (pH=7.0) solution containing 1 mmol / L functional monomer 3-aminophenylboronic acid, and a saturated calomel electrode was used as a reference electrode and a platinum wire was used as a counter electrode. The CV method was used to cycle 20 times in the voltage range of -1.5~0.5 V and the scanning rate was 100 mV / s to form a molecularly imprinted polymer film. Then, the molecularly imprinted polymer film was placed in 0.1 mol iodine containing 2.5 mmol / L chrome black T. In l / L PBS solution, with saturated calomel electrode as reference electrode and platinum wire as counter electrode, chrome black T was electropolymerized at -0.4~1.5V by CV method, and 2~5 cycles of scanning polymerization were carried out with a scanning rate of 100mV / s. pAPBA and pEBT were electropolymerized on the surface of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT.

[0018] S9. Wash away the free EBT with ultrapure water, and then elute the VEGF protein template with a 0.1 mol / L PBS (pH = 5.0) solution containing 5% (v / v) methanol to form a specific imprinting cavity that complements the VEGF protein molecular structure. Finally, rinse with ultrapure water to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT~SMIP, abbreviated as ANE / / pFA / / SMIP.

[0019] In order to achieve sensitive and specific detection of VEGF protein, several important parameters were optimized. For comparison, after ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs, ANE / / pFA / / SMIP and ANE / / pFA / / SMIP were incubated again in VEGF protein solution (denoted as ANE / / pFA / / SMIP with VEGF), the peak currents of differential pulse voltammetry (DPV) were defined as I1, I2 and I3, respectively.

[0020] Preferably, the number of cycles of electropolymerization of ferulic acid is 10; when the number of cycles is 5-10, the I1 value gradually increases, and when the polymerization is carried out to 10 cycles, the I1 value reaches the maximum. When the number of cycles continues to increase, the I1 value changes very little and remains almost unchanged. This is probably because after 10 cycles, the excessive pFA thickness hinders electron transfer. Since the sensitivity is closely related to the peak current of pFA, the optimal number of cycles is selected to be 10.

[0021] Preferably, the incubation time in the 4-mercaptophenylboronic acid solution is 100 minutes. During the 100-minute incubation time, the peak current reaches a maximum, which may be due to the suitable assembly density of the 4-mercaptophenylboronic acid solution for electron transfer and VEGF protein. The self-assembled 4-mercaptophenylboronic acid solution is closely related to the amount of VEGF protein, and the incubation time of 100 minutes is selected to obtain the best protein binding amount.

[0022] Preferably, the incubation time of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA in the VEGF protein solution is 8 hours. The I2 value reaches a maximum value at 8 hours, which may be due to the saturation of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA binding to VEGF protein, that is, the binding to VEGF protein through interaction reaches a saturation equilibrium after incubation for 8 hours.

[0023] Preferably, the electropolymerization cycle of chrome black T is 4. When the polymerization exceeds 4 cycles, the value of I2 is significantly reduced, which is because the elution of the template VEGF protein becomes difficult with the thickness of the excess pEBT (polychrome black T), so 4 cycles are selected as the pEBT electropolymerization of SMIP.

[0024] Preferably, the elution time is ≥ 2.5 h. The value of I2 increases with the increase of elution time and does not change much after 2.5 h, indicating that 2.5 h is sufficient to remove the template VEGF protein.

[0025] The present invention also provides an application of a micro-electrochemical sensor in detecting VEGF, and the application method is: placing the needle tip of the micro-electrochemical sensor in a 0.02 mol / L PBS solution (pH=7.4) containing different concentrations of VEGF protein, incubating at 4°C for 2-3 hours, washing the needle tip surface with a 0.02 mol / L PBS solution to remove physically adsorbed protein; then placing the needle tip of the micro-electrochemical sensor in a 0.1 mol / L PBS (pH=5.0-9.0) solution, detecting the electrochemical signal after binding to the VEGF protein with DPV at room temperature, drawing a working curve according to the current-endothelial growth factor protein concentration, and calculating the concentration of the unknown endothelial growth factor protein according to the working curve and the current.

[0026] Preferably, when the VEGF protein is detected, the pH value of the detection solution is 7.0. When the pH value increases from 5.0 to 7.0, the current response change value gradually increases; when the pH value increases from 7.0 to 9.0, the current response change value gradually decreases. On this basis, the optimal pH value of the VEGF protein detection solution is determined to be 7.0.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention prepares a micro electrochemical sensor for detecting VEGF on an acupuncture needle. The micro electrochemical sensor uses AuNPs and MWNTs to provide a large specific surface area and high conductivity. The signal comes from the electronic medium pFA embedded in the surface molecular imprinting polymer. The interface function is mainly constructed through the green pathway of electropolymerization and molecular self-assembly (incubation). The VEGF molecule is anchored through the interaction with 4-MPBA, and then 3-APBA is used to specifically and stably adsorb VEGF, and then pEBT is used to achieve the selective binding of the specific imprinting cavity to VEGF.

[0029] Electrons can be transferred smoothly in the specific imprinted cavity, and rebinding VEGF in the specific imprinted cavity hinders the electron transfer in pFA. The concentration of bound VEGF in the specific imprinted cavity is determined by the current of electron transfer.

[0030] 2. The micro-electrochemical sensor of the present invention shows good detection performance and stability. In addition, the micro-electrochemical sensor may be combined with traditional acupuncture technology in the future, which has long-term research significance.

[0031] 3. The micro-electrochemical sensor of the present invention adopts molecular imprinting technology, which is very similar to the "lock and key theory" of enzymes. After elution of the VEGF imprinting interface, a specific imprinting cavity is formed in the micro-electrochemical sensor, which has a very high selective binding effect on the target analyte VEGF.

[0032] 4. Electrochemical sensors have the advantages of low cost, high sensitivity and easy operation, and have received extensive attention in biomedical research. Electrodes commonly used in electrochemical sensors include glassy carbon electrodes, screen-printed carbon electrodes, gold electrodes, platinum electrodes and carbon fiber electrodes. Compared with traditional electrodes, stainless steel acupuncture needles have small size, thin tips and appropriate electrochemical properties; compared with carbon fiber electrodes, stainless steel acupuncture needles are longer and tougher, and are easy to combine with acupuncture techniques. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a flow chart for the production of the micro electrochemical sensor ANE / / pFA / / SMIP of the present invention.

[0034] Figure 2 This is the sample of Example 1 of the present invention, wherein (a) is a scanning electron microscope image of ANE; (b) is a scanning electron microscope image of ANE / AuNPs.

[0035] Figure 3 This is the sample of Example 1 of the present invention, wherein (a) is a scanning electron microscope image of ANE / AuNPs / pEDOT~MWNTs; (b) is a scanning electron microscope image of ANE / AuNPs / pEDOT~MWNTs / pFA; (c) is a scanning electron microscope image of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs; (d) is a scanning electron microscope image of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF; (e) is a scanning electron microscope image of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT; (f) is a scanning electron microscope image of ANE / / pFA / / SMIP.

[0036] Figure 4 Spectra of ANE and ANE / AuNPs of Example 1 of the present invention.

[0037] Figure 5ANE, ANE / AuNPs and ANE / AuNPs~pEDOT~MWNTs, ANE / AuNPs / pEDOT~MWNTs / pFA, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT and ANE / / pFA / / SMIP were prepared in 0.1 mol / L KCl solution and 5.0 mmol / L [Fe(CN)6] 3- / 4- Cyclic voltammograms in solution.

[0038] Figure 6 Cyclic voltammograms of ANE / AuNPs / PEDOT~MWNTs / pFA, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT and ANE / / pFA / / SMIP in 0.1 mol / L PBS solution (pH=7.0).

[0039] Figure 7 shows the differential pulse voltammograms of micro-electrochemical sensors of ANE / AuNPs / PEDOT~MWNTs / pFA, ANE / AuNPs / PEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT, ANE / / pFA / / SMIP and ANE / / pFA / / SMIP re-adsorbing VEGF in 0.1 mol / L PBS solution (pH=7.0).

[0040] Figure 8 Differential pulse voltammograms of ANE / AuNPs / PEDOT~MWNTs / pFA, ANE / AuNPs / PEDOT~MWNTs / pFA~AuNPs~4-MPBA, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA@p-APBA~pEBT of comparative example 1, and ANE / / pFA / / NIP of comparative example 1 in 0.1 mol / L PBS solution (pH=7.0).

[0041] Fig. 9This is the sample of Example 1 of the present invention, wherein (a) is the CV diagram of ANE / AuNPs / pEDOT-MWNTs / pFA in 0.1 mol / L PBS solution (pH=7.0); (b) is the linear diagram of oxidation peak current and scan rate obtained through (a).

[0042] Fig.10 This is the sample of Example 1 of the present invention, wherein (a) is a graph showing the number of pFA polymerization circles; (b) is a graph showing the incubation time in 4-MPBA; (c) is a graph showing the incubation time in VEGF protein; (d) is a graph showing the number of pE BT polymerization circles; (e) is a graph showing the elution time; and (f) is a graph showing the rebinding time of VEGF protein.

[0043] Fig.11 This is the current diagram of ANE / / pFA / / SMIP in Example 1 of the present invention in VEGF protein solutions of different pH values.

[0044] Fig.12 This is the sample of Example 1 of the present invention, wherein (a) is a DPV curve of ANE / / pFA / / SMIP after incubation in 0.02 mol / L PBS solution (pH=7.4) containing different concentrations of VEGF; (b) is a linear relationship diagram between ΔI value and the logarithm of VEGF concentration.

[0045] Fig.13 This is the sample of Example 1 of the present invention, wherein (a) is an interference analysis diagram of ANE / / pFA / / SMIP; (b) is a stability analysis diagram of ANE / / pFA / / SMIP; (c) is a reproducibility analysis diagram of ANE / / pFA / / SMIP. DETAILED DESCRIPTION

[0046] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0047] The present invention also uses a micro-electrochemical sensor without incubating VEGF for comparative research. The micro-electrochemical sensor obtained at this time does not contain an imprinted layer-specific imprinted cavity, that is, a non-imprinted layer; the results show that electrons can be smoothly transferred in the specific imprinted cavity, but the non-imprinted layer will hinder the electron transfer of pFA.

[0048] The technical solution of the present invention is studied by using embodiments and comparative examples, which are specifically as follows:

[0049] Example 1

[0050] Preparation methods of micro electrochemical sensors, such as Figure 1 As shown, the following steps are included:

[0051] S1. In a typical processing process, a stainless steel acupuncture needle (AN) was polished in the same direction using fine sandpaper for 3 min. Next, the polished acupuncture needle was immersed in anhydrous ethanol and ultrasonically cleaned for 10 min. The treated acupuncture needle was immersed in ultrapure water for ultrasonic cleaning for 10 min and dried naturally in the air to obtain a bare needle electrode (ANE).

[0052] S2. Modify gold nanoparticles on the ANE tip using cyclic voltammetry: immerse the bare needle electrode in 2.5 mmol / L chloroauric acid solution for electrodeposition, and use cyclic voltammetry (CV) to cycle 5 times in the potential range of -1.5 to 0.5 V with a scan rate of 25 mV / s. After the deposition is completed, rinse the tip surface with ultrapure water to obtain ANE / AuNPs.

[0053] S3. Deposit carbon nanotubes using a constant potential method: Place ANE / AuNPs in a mixed solution of 2 mg / L carboxylated multi-walled carbon nanotubes and 0.02 mol / L 3,4-ethylenedioxythiophene (EDOT) for deposition at a potential of 1.2 V for 100 s to obtain ANE / AuNPs / pEDOT-MWNTs.

[0054] S4. FA was electropolymerized using the CV method. ANE / AuNPs / pEDOT-MWNTs were placed in a PBS solution (pH = 4.5) containing 0.4 mmol / L of ferulic acid. The solution was circulated for 10 cycles within a voltage range of -0.25 to 0.75 V with a scan rate of 20 mV / s (before starting the polymerization, nitrogen was bubbled into the PBS solution containing 0.4 mmol / L of ferulic acid to completely deoxygenate it) to obtain ANE / AuNPs / pEDOT-MWNTs / pFA.

[0055] S5. Immerse ANE / AuNPs / pEDOT~MWNTs / pFA in 2.5mmol / L chloroauric acid solution for electrodeposition. Cyclic voltammetry is used to cycle 3 times in the potential range of -1.5~0.5V with a scan rate of 25mV / s. After the deposition is completed, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs are obtained.

[0056] S6. Place ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs in 4-mercaptophenylboric acid solution and incubate at 4°C for 100 min to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA.

[0057] S7. Place ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA in a VEGF protein solution (the amount of VEGF protein solution is 10 μg / mL), incubate at 4°C for 8 h, and obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF.

[0058] S8, immersing ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF in a 0.1 mol / L PBS (pH=7.0) solution containing 1 mmol / L functional monomer 3-aminophenylboronic acid, and circulating 20 times in a voltage range of -1.5~0.5V by CV method, with a scanning rate of 100 mV / s, to form a molecularly imprinted polymerized film, then placing the molecularly imprinted polymerized film in an electrolyte of 0.1 mol / L PBS solution containing 2.5 mmol / L chrome black T, and electropolymerizing chrome black T (EBT) by CV method in a voltage range of -0.4~1.5V, and performing 4 cycles of scanning polymerization at a scanning rate of 100 mV / s, to obtain

[0059] ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT.

[0060] S9. Wash away the free EBT with ultrapure water, and then elute the VEGF protein template with a 0.1 mol / L PBS (pH = 5.0) solution containing 5% (v / v) methanol to form a specific imprinting cavity that complements the VEGF protein molecular structure. Finally, rinse with ultrapure water to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT~SMIP, abbreviated as ANE / / pFA / / SMIP.

[0061] Comparative Example 1

[0062] The preparation steps are the same as those in Example 1, except that the VEGF incubation in step S7 is not performed, and the steps include:

[0063] S1. In a typical processing process, a stainless steel acupuncture needle (AN) was polished in the same direction using fine sandpaper for 3 min. Next, the polished acupuncture needle was immersed in anhydrous ethanol and ultrasonically cleaned for 10 min. The treated acupuncture needle was immersed in ultrapure water for ultrasonic cleaning for 10 min and dried naturally in the air to obtain a bare needle electrode (ANE).

[0064] S2. Modify gold nanoparticles on the ANE tip using cyclic voltammetry: immerse the bare needle electrode in 2.5 mmol / L chloroauric acid solution for electrodeposition, and use cyclic voltammetry (CV) to cycle 5 times in the potential range of -1.5 to 0.5 V with a scan rate of 25 mV / s. After the deposition is completed, rinse the tip surface with ultrapure water to obtain ANE / AuNPs.

[0065] S3. Deposit carbon nanotubes using a constant potential method: Place ANE / AuNPs in a mixed solution of 2 mg / L carboxylated multi-walled carbon nanotubes and 0.02 mol / L 3,4-ethylenedioxythiophene (EDOT) for deposition at a potential of 1.2 V for 100 s to obtain ANE / AuNPs / pEDOT-MWNTs.

[0066] S4. FA was electropolymerized using the CV method. ANE / AuNPs / pEDOT-MWNTs were placed in a PBS solution (pH = 4.5) containing 0.4 mmol / L of ferulic acid. The solution was circulated for 10 cycles within a voltage range of -0.25 to 0.75 V with a scan rate of 20 mV / s (before starting the polymerization, nitrogen was bubbled into the PBS solution containing 0.4 mmol / L of ferulic acid to completely deoxygenate it) to obtain ANE / AuNPs / pEDOT-MWNTs / pFA.

[0067] S5. Immerse ANE / AuNPs / pEDOT~MWNTs / pFA in 2.5mmol / L chloroauric acid solution for electrodeposition. Cyclic voltammetry is used to cycle 3 times in the potential range of -1.5~0.5V with a scan rate of 25mV / s. After the deposition is completed, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs are obtained.

[0068] S6. Place ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs in 4-mercaptophenylboric acid solution and incubate at 4°C for 100 min to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA.

[0069] S7, immersing ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA in a 0.1 mol / L PBS (pH=7.0) solution containing 1 mmol / L functional monomer 3-aminophenylboronic acid, and circulating 20 times in a voltage range of -1.5 to 0.5 V by CV method, with a scanning rate of 100 mV / s, to form a molecularly imprinted polymerized film, then placing the molecularly imprinted polymerized film in an electrolyte of 0.1 mol / L PBS solution containing 2.5 mmol / L chrome black T, and electropolymerizing chrome black T (EBT) by CV method in a voltage range of -0.4 to 1.5 V, and performing 4 cycles of scanning polymerization at a scanning rate of 100 mV / s, to obtain

[0070] ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA@p-APBA~pEBT.

[0071] S8. Wash away the free EBT with ultrapure water, then elute with 0.1 mol / L PBS (pH = 5.0) solution containing 5% (v / v) methanol, and finally rinse with ultrapure water to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA@p-APBA~pEBT~SMIP, abbreviated as ANE / / pFA / / NIP.

[0072] The following study is conducted by taking the ANE / / pFA / / SMIP of Example 1 as an example, and comparing it with the ANE / / pFA / / NIP of Comparative Example 1. The specific study methods and results are as follows:

[0073] 1. Morphology characterization and elemental analysis:

[0074] Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were used to characterize the surface morphology and composition of the micro-electrochemical sensor. Figure 2 Figure (a) shows that the surface morphology of the ANE tip shows longitudinal scratches. These scratches are caused by polishing. The polishing of stainless steel acupuncture needles is conducive to the subsequent modification of nanomaterials. Figure 2 As shown in Figure (b), AuNPs are evenly distributed on the surface of ANE, and the diameter of AuNPs is about 60nm. Figure 4 The characteristic peaks of metallic Au can be clearly seen, confirming that AuNPs were successfully modified onto ANE. Figure 4The energy dispersive X-ray spectroscopy (EDS) of ANE / AuNPs reveals the presence of Cr, Mn, Ni, Fe (from ANE itself) and Au elements. The presence of Au further confirms the deposition of AuNPs on the surface of ANE, which can provide a large specific surface area and high conductivity for subsequent modification.

[0075] Next, MWNTs were electrodeposited on ANE / AuNPs using a constant potential method. Figure 3 Figure (a) shows the SEM image of ANE / AuNPs / pEDOT~MWNTs, and it is clear that a clear network structure and smooth surface appear on the surface of ANE / AuNPs. Then, FA is electropolymerized on the surface of ANE / AuNPs / pEDOT~MWNTs. Figure 3 Figure (b) clearly shows the pFA polymerized on the surface of carbon nanotubes. The SEM image of the secondary deposited Au nanoparticles is shown in Figure 2. Figure 3 As shown in Figure (c), it is clearly seen that gold nanoparticles are attached to the surface of ANE / AuNPs / pEDOT~MWNTs~pFA. The images of ANE / AuNPs / pED OT~MWNTs / pFA~AuNPs~4-MPBA~VEGF, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT and ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT~SMIP are shown in Figure 5. Figure 3 As shown in (d, (e), and (f), it can be seen that the removal of VEGF protein makes the surface of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT~SMIP rough, which is attributed to the formation of imprinted cavities on its surface.

[0076] 2. Electrochemical behavior of various interfaces:

[0077] CV was used to further characterize the modification of AN. Figure 5 It shows that ANE, ANE / AuNPs and ANE / AuNPs~MWNTs in the presence of 5.0mmol / L [Fe(CN)6] 3- / 4- CV graphs in 0.1 mol / L KCl solution. 3- / 4-The heterogeneous electron transfer process of the redox probe was suppressed by the stainless steel surface material, and ANE showed a rather low peak current. The peak current increased significantly at ANE / AuNPs, which was attributed to the enhanced heterogeneous electron transfer performance after electrodeposition of AuNPs. The peak current of ANE / AuNPs / pEDOT~MWNTs increased slightly, which was attributed to the presence of MWNTs on the surface, which not only increased the specific surface area and improved the conductivity, but also served as a good carrier for fixing SMIP.

[0078] CV graphs of ANE / AuNPs / PEDOT~MWNTs / pFA, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT and ANE / / pFA / / SMIP in 0.1 mol / L PBS solution (pH=6.0) are shown in Figure 2. Figure 6 As shown. A pair of clear, quasi-reversible redox peaks appeared at the interface after pFA modification. When p-APBA was further modified with pEBT, the microelectrochemical sensor had no obvious electrochemical response in PBS solution. However, in the ANE / / pFA / / SMIP obtained after elution, the interface had a relatively obvious electrochemical response in PBS solution, indicating the formation of imprinted cavities.

[0079] Figure 7 shows the differential pulse voltammograms (DPV) of ANE / AuNPs / PEDOT~MWNTs / pFA, ANE / AuNPs / PEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF, ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT, ANE / / pFA / / SMIP and ANE / / pFA / / SMIP re-adsorbing VEGF in 0.1 mol / L PBS solution (pH=7.0). Due to the oxidation of pFA, there is a significant oxidation peak on the DPV of ANE / AuNPs / pEDOT~MWNTs / pFA. After self-assembly modification of 4-MPBA and VEGF, the oxidation peak decreases, which also indicates that the template VEGF protein is successfully anchored on the electrode. After electropolymerization of p-APBA and pEBT, an imprinted membrane was formed. Due to the poor conductivity of the two, the peak current of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT was significantly reduced. After eluting the VEGF protein template, the peak current increased, which was attributed to the formation of an imprinted cavity complementary to the shape of the VEGF protein template, which promoted charge transfer. After the prepared microelectrochemical sensor was incubated again in the VEGF protein solution (ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT~SMIP with VEGF in the figure), the VEGF protein in the solution was captured by the imprinted hole, and the peak current decreased again.

[0080] The current of ANE / / pFA / / NIP and ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA@p-APBA~pEBT in Comparative Example 1 changed little before and after elution, which is due to the absence of imprinted cavities in ANE / / pFA / / NIP. Figure 8 shown.

[0081] In order to study the electrochemical oxidation mechanism of pFA on the ANE / AuNPs / PEDOT-MWNTs / pFA electrode, cyclic voltammetry curves were recorded in the range of scan speed from 10 mV / s to 300 mV / s, as shown in Figure 2. Fig. 9 As shown in Figure (a), the oxidation peak current of FA increases with the increase of scanning speed, and the oxidation peak potential gradually shifts to the right. Fig. 9 Figure (b) shows that there is a linear relationship between the oxidation peak current and the scan rate, and the relationship is I pa (μA)=1.21043v(mV / s)+0.05729, R 2=0.9964. The linear equation shows that the electrochemistry of pFA on the ANE / AuNPs / pEDOT-MWNTs / pFA electrode is an adsorption-controlled process.

[0082] 3. Optimization of preparation conditions of micro-electrochemical sensors:

[0083] In order to achieve sensitive and specific detection of VEGF protein, several important parameters were optimized. For comparison, after ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs, ANE / pFA / / SMIP and ANE / / pFA / / SMIP were incubated again in VEGF protein solution, the peak currents of DPV were defined as I1, I2 and I3, respectively.

[0084] (1) Number of FA turns: Fig.10 Figure (a) shows the relationship between I1 and the number of pFA electropolymerization cycles. When the number of polymerization cycles is 5-10, the I1 value gradually increases, and when the polymerization is carried out to 10 cycles, the I1 value reaches the maximum. When the number of polymerization cycles continues to increase, the I1 value changes very little and remains almost unchanged. This is probably because after 10 cycles, the excess pFA thickness hinders electron transfer. Since the sensitivity is closely related to the peak current of pFA, the optimal number of polymerization cycles is selected as 10 cycles.

[0085] (2) Incubation time of 4-MPBA solution: Fig.10 Figure (b) shows the relationship between the I2 value and the incubation time of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs in 4-MPBA solution. The peak current value reaches the maximum within the incubation time of 100 minutes, which may be due to the suitable assembly density of 4-MPBA solution for electron transfer and VEGF protein. The amount of self-assembled 4-MPBA and VEGF protein is closely related, and the incubation time of 100 minutes is selected to obtain the optimal protein binding amount.

[0086] (3) Protein incubation time: Fig.10 As shown in Figure (c), the I2 value reaches the maximum at 8 h, which may be due to the saturation of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-PBA on the protein. In other words, the immobilization of the VEGF protein template through interaction reaches saturation after incubation for 8 h.

[0087] (4) Number of pEBT polymerization cycles: The relationship between I2 and the number of EBT electropolymerization cycles is shown in Fig.10 As shown in Figure (d), when the polymerization exceeds 4 cycles, the value of I2 decreases significantly, which is because the elution of the template becomes difficult with the excess pEBT thickness. Therefore, 4 cycles of pEBT electropolymerization as SMIP were selected.

[0088] (5) Template molecule elution time: Fig.10 Figure (e) shows the effect of elution time on I2. I2 increased with elution time and did not change much after 2.5 h, indicating that 2.5 h was sufficient to remove the VEGF protein template.

[0089] (6) Second protein incubation time: Fig.10 Figure (f) shows the relationship between ΔI (ΔI=I2-I3) and the rebinding time of VEGF protein. At the rebinding time of 2.5h, the ΔI value reaches the maximum, indicating that the binding of VEGF protein to the imprinted cavity reaches saturation after 2.5h.

[0090] (7) Detection solution pH: In the process of VEGF protein detection, the detection solution pH is a key factor affecting the current response. The effect of the detection solution pH on the current response was studied in the range of pH 5.0, 6.0, 7.0, 8.0, and 9.0. Fig.11 As shown in the figure, when the pH value rises from 5.0 to 7.0, the current response change value gradually increases; when the pH value rises from 7.0 to 9.0, the current response change value gradually decreases. On this basis, it is determined that the optimal pH value of the detection solution is 7.0.

[0091] 4. Calibration curve:

[0092] Under optimized conditions, the prepared micro-electrochemical sensor was used to detect VEGF protein. Fig.12 Figure (a) shows the DPV of the microelectrochemical sensor after incubation in solutions containing different concentrations of VEGF. As the VEGF concentration increases, the peak current of pFA gradually decreases. The decrease in pFA current may be due to the gradual occupation of the interface imprinting cavity by the VEGF protein in the solution, resulting in the obstruction of electron transfer. The decrease in value is positively correlated with the increase in VEGF concentration. The results show that there is a good linear relationship between the ΔI (ΔI = I2-I3) value and the VEGF concentration, as shown in Figure 2. Fig.12 The linear range is 0.25-1000 ng / mL, 0 ng / mL, 0.25 ng / mL, 0.5 ng / mL, 1.0 ng / mL, 5.0 ng / mL, 10 ng / mL, 50 ng / mL, 100 ng / mL, 500 ng / mL and 1000 ng / mL, the detection limit is 10 pg / mL (S / N=3), and the linear regression equation is ΔI=1.18759lgC+0.76242(R 2 =0.9958).

[0093] In addition, the performance of the micro-electrochemical sensor was compared with the reported micro-electrochemical sensor for detecting VEGF, and the results are listed in Table 1. By comparison, the micro-electrochemical sensor of the present invention has a lower detection limit and a wider linear range, indicating that the micro-electrochemical sensor has a good potential in detecting VEGF protein.

[0094] Table 1. Comparison of the effects of different electrochemical sensors in detecting VEGF

[0095]

[0096] References

[0097] 【1】Fu XM, Liu ZJ, Cai SX, et al. Electrochemical aptasensor for the detection of vascular endothelial growth factor (VEGF) based on DNA-templatedAg / Pt bimetallic nanoclusters[J]. Chinese Chemical Letters, 2016, 27(6):920-926.

[0098] 【2】Ni SN, Qiao LC, Shen ZP, et al.Physical absorption vs covalentbinding of graphene oxide on glassy carbon electrode towards a robustaptasensor for ratiometric electrochemical detection of vascular endothelialgrowth factor (VEGF) in serum[J].Electrochimica Acta,2020,331:135321.

[0099] 【3】He M T,Luo P,Xie Y Y,et al.Electrochemical determinationofvascular endothelial growth factor using functional metal-polymernanocomposites[J].Colloids and Surfaces A:Physicochemical and EngineeringAspects,2023,677:132380.

[0100] 【4】Lee J,Tatsumi A,Tsukakoshi K,et al.Application of a GlucoseDehydrogenase-Fused with Zinc Finger Protein to Label DNA Aptamers for theElectrochemical Detection ofVEGF[J].Sensors,2020,20(14):3878.

[0101] 【5】Pan L H,Kuo S H,Lin T Y,et al.An electrochemical biosensor tosimultaneously detect VEGF and PSA for early prostate cancer diagnosis basedon graphene oxide / ssDNA / PLLA nanoparticles[J].Biosensors and Bioelectronics,2017,89:598-605.

[0102] 【6】Mei C Y,Zhang Y Y,Pan L,et al.A One-Step ElectrochemicalAptasensor Based on Signal Amplification of Metallo Nanoenzyme Particles forVascular Endothelial Growth Factor[J].Frontiers in Bioengineering andBiotechnology,2022,10:850412.

[0103] 【7】Kim GI, Kim KW, Oh MK, et al. Electrochemical detection of vascularendothelial growth factors (VEGFs) using VEGF antibody fragments modified AuNPs / ITO electrode [J]. Biosensors and Bioelectronics, 2010, 25(7): 1717-1722.

[0104] 5. Study on the selectivity and stability of micro-electrochemical sensors:

[0105] When testing the selectivity of the microelectrochemical sensor, ion interferents with a concentration of 1 μg / mL were added to the detection solution, including S protein (SARS-CoV-2), mesothelin (MSLN), osteopontin (OPN), bovine serum albumin (BSA), dopamine (DA), uric acid (UA), Cl - Mg 2+ Or Na + . Take SARS-CoV-2, MSLN, OPN, BSA, UA, DA, Cl-, Mg 2+ Or Na + (1 μg / mL) and possible coexisting substances as interferences to study the specificity of the microelectrochemical sensor in detecting the same concentration of VEGF. Fig.13 As shown in Figure (a), the obtained ΔI (ΔI=I2-I3) is significantly lower than the response value of VEGF, indicating that the micro-electrochemical sensor has excellent specificity.

[0106] Five micro electrochemical sensors were prepared to detect 1 μg / mL VEGF under the same conditions to evaluate the reproducibility. Fig.13 As shown in Figure (b), the value of ΔI (ΔI=I2-I3) changes very little, and the relative standard deviation (RSD) is 0.81%, indicating that the micro-electrochemical sensor has good reproducibility.

[0107] When testing the stability of the micro-electrochemical sensor, the micro-electrochemical sensor that has been tested for the first time was stored at room temperature, and the DPV test was performed on the micro-electrochemical sensor again after 1 day, 3 days, 5 days, 7 days, 10 days, and 15 days, and the current was compared with the peak value of the first test. The stability of the micro-electrochemical sensor was studied, and the results are as follows: Fig.13 As shown in Figure (c) in Figure 1, the I2 value remained basically unchanged in the first 7 days and maintained 83% of the initial value after 15 days. The results show that the prepared micro-electrochemical sensor has high stability.

[0108] 6. Sample testing:

[0109] Using a micro-electrochemical sensor, the VEGF protein in three clinical serum samples was detected by the standard addition method. The results are shown in Table 2.

[0110] Table 2. Detection table of VEGF in blood samples

[0111] Sample No. Addition amount (ng / mL) Detection amount (ng / mL) Recovery rate (%) 1 10.0 10.2 101.8 2 30.0 30.8 102.5 3 50.0 47.8 95.7

[0112] The results in Table 2 show that the recovery rate is in the range of 95.7% to 102.5%, and the relative standard deviation (RSD) does not exceed 1.00%, which proves that the prepared micro-electrochemical sensor has the reliability for clinical testing.

[0113] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a micro electrochemical sensor, characterized in that: The steps include: S1, placing the tip of the acupuncture needle in a chloroauric acid solution for electrodeposition to obtain ANE / AuNPs; S2, placing the tip of ANE / AuNPs in a mixed solution of multi-walled carbon nanotubes and 3,4-ethylenedioxythiophene for electrodeposition to obtain ANE / AuNPs / pEDOT~MWNTs; S3, placing the tip of ANE / AuNPs / pEDOT~MWNTs in an oxygen-free PBS solution containing ferulic acid for electrodeposition to obtain ANE / AuNPs / pEDOT~MWNTs / pFA; S4, placing the needle tip of ANE / AuNPs / pEDOT~MWNTs / pFA in a chloroauric acid solution for electrodeposition to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs; S5, placing the needle tip of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs in a 4-mercaptophenylboric acid solution for incubation to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA; S6, placing the needle tip of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA in a vascular endothelial growth factor protein solution and incubating to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF; S7, soaking the needle tip of ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF in a PBS solution containing 3-aminophenylboronic acid for electrodeposition to obtain a molecularly imprinted polymer film, and then placing the molecularly imprinted polymer film in a PBS solution containing chrome black T for electrodeposition to obtain ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT; S8. Elute the vascular endothelial growth factor protein on ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF@p-APBA~pEBT to form a specific imprinting cavity that complements the molecular structure of the vascular endothelial growth factor protein, and obtain a micro electrochemical sensor.

2. The method for preparing a micro electrochemical sensor according to claim 1, characterized in that: In step S1 and step S4, the electrodeposition method is: using acupuncture needles or ANE / AuNPs / pEDOT-MWNTs / pFA as working electrodes, together with reference electrodes and counter electrodes to form a three-electrode system, using cyclic voltammetry, and cycling at -1.5 to 0.5 V for 3 to 5 cycles.

3. The method for preparing a micro electrochemical sensor according to claim 1, characterized in that: In step S2, the electrodeposition method is: using ANE / AuNPs as a working electrode, a reference electrode and a counter electrode to form a three-electrode system, using a constant current method, and electrodepositing at a potential of 1.1 to 1.3 V for 80 to 120 seconds.

4. The method for preparing a micro electrochemical sensor according to claim 1, characterized in that: In step S3, the electrodeposition method is: using ANE / AuNPs / pEDOT-MWNTs as a working electrode, a reference electrode and a counter electrode to form a three-electrode system, using cyclic voltammetry, and cycling at -0.25 to 0.75 V for ≥10 cycles.

5. The method for preparing a micro electrochemical sensor according to claim 1, characterized in that: In step S5, the incubation conditions are: incubation at 4°C for 90 to 120 minutes.

6. The method for preparing a micro electrochemical sensor according to claim 1, characterized in that: In step S6, the incubation conditions are: incubation at 4° C. for 7 to 9 hours.

7. The method for preparing a micro electrochemical sensor according to claim 1, characterized in that: In step S7, the electrodeposition method in the PBS solution containing 3-aminophenylboronic acid is: ANE / AuNPs / pEDOT~MWNTs / pFA~AuNPs~4-MPBA~VEGF is used as the working electrode, together with the reference electrode and the counter electrode to form a three-electrode system, and cyclic voltammetry is used to cycle 20 times at -1.5~0.5V.

8. The method for preparing a micro electrochemical sensor according to claim 1, characterized in that: In step S7, the electrodeposition method in the PBS solution containing chrome black T is: using the molecular imprinted polymer film as a working electrode, a reference electrode and a counter electrode to form a three-electrode system, using cyclic voltammetry, and cycling at -0.4 to 1.5 V for 2 to 5 cycles.

9. A micro electrochemical sensor prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the micro electrochemical sensor according to claim 9 in preparing a sensor for detecting vascular endothelial growth factor, characterized in that: The application method is: The needle tips of the micro electrochemical sensors were placed in 0.02 mol / L PBS solutions containing different concentrations of vascular endothelial growth factor protein, respectively, and incubated at 4°C for 2 to 3 hours, and then the needle tip surfaces of the micro electrochemical sensors were washed to obtain incubated sensors; The incubated sensor was placed in a PBS solution, and the electrochemical signal was detected by differential pulse voltammetry at room temperature, and a working curve was drawn according to the current-endothelial growth factor protein concentration; Calculate the concentration of unknown endothelial growth factor protein based on the working curve and electrochemical signal.

Citation Information

Cited By

  • Dual collaborative recognition nerve probe based on acupuncture needle extension grid and preparation method and application thereof

    CN122423868A